PENGARUH PRODUK DOMESTIK BRUTO, INFLASI DAN INDEX HARGA SAHAM GABUNGAN TERHADAP HARGA SAHAM SYARIAH (STUDI EMPIRIS PADA HARGA SAHAM GABUNGAN JAKARTA ISLAMIC INDEX TAHUN 2015 – 2017) - Elfina Rahmania; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the effect of Gross Domestic Product, inflation and the composite stock price index on Sharia Composite Stock Prices. The variables used in this study are GDP, Inflation, IHSG and Islamic joint stock prices. The method used to analyze is multiple linear regression test. With t test and F test as hypothesis testers. The population and sample in this study are companies listed in the Jakarta Islamic Index in 2018. The results of the study show that gross domestic product has no significant negative effect, inflation has a significant negative effect, and JCI has a significant positive effect. Keywords: Sharia Stock Price, Jakarta Islamic Index, Gross Domestic Product, Inflation, Composite Stock Price Index